2015
DOI: 10.1007/s10921-015-0287-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive Electrical Methods for Measuring the Physical Characteristics of Porous Materials

Abstract: The durability of reinforced concrete structures, built on the seafront, has been at the heart of recent concerns. Indeed, chloride transport across the porosity of concrete coating produces medium to long-term corrosion of reinforcements. This has a direct impact on the mechanical behavior and the ageing of the affected structures. The difficulty of in situ monitoring of these structures, continuously and non-destructively against infiltration of chlorides, is still topical. The work presented here aims mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…According to Archie's law [24], the formation parameter can be replaced by the porosity with a power law. From Merioua et al [23], for mortar with W/C equal to 0.5 m is approximately 3.…”
Section: Comparison Of the Damage Index And Change In The Mechanical mentioning
confidence: 91%
See 3 more Smart Citations
“…According to Archie's law [24], the formation parameter can be replaced by the porosity with a power law. From Merioua et al [23], for mortar with W/C equal to 0.5 m is approximately 3.…”
Section: Comparison Of the Damage Index And Change In The Mechanical mentioning
confidence: 91%
“…The frequency of the alternating current can affect the resistivity results significantly [26]. As investigated by Merioua et al [23], to assure the ohm's law is valid, the range of appropriate frequencies is 500 Hz-50 kHz. Additionally, the polarization effect can greatly affect the resistivity and it is highly dependent on frequency; to reduce the effect to be minimum, the frequency used in this study was 1 kHz, which is the optimized frequency reported by McCarter et al [35] on the study of concrete under FTCs.…”
Section: Test Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…The specification of the service-life/performance/durability of reinforced concrete by means a single parameter is the holy grail of the engineer and hence a subject of intense research interest (see, for example, Neithalath, Persun, and Manchiryal, 2010;Muigai, Moyo and Alexander, 2012;Spragg et al, 2013;Andrade, d'Andrea and Rebolledo, 2014;Nganga, Alexander and Beushausen, 2015;Merioua, Bezzar and Ghomari, 2015). The challenges posed by a performance-based testing and specification approach to improve service life of concrete structures have been acknowledged (Beushausen and Fernandez-Luco, 2015).…”
Section: Performance Testingmentioning
confidence: 99%